2019
DOI: 10.7717/peerj.7144
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptera genome and transcriptome sequences reveal numerous differences in neuropeptide signaling between species

Abstract: Background Insect neuropeptides are interesting for the potential their receptors hold as plausible targets for a novel generation of pesticides. Neuropeptide genes have been identified in a number of different species belonging to a variety of insects. Results suggest significant neuropeptide variation between different orders, but much less is known of neuropeptidome variability within an insect order. I therefore compared the neuropeptidomes of a number of Coleoptera. Methodology Publicly available genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 90 publications
(116 reference statements)
1
94
0
Order By: Relevance
“…Moreover, we observed that most of the particular paralogues and splicing variants initially detected in B. mori seem to be a characteristic of Lepidoptera rather than a possible consequence of domestication of the silkworm, as previously hypothesized (Roller et al, 2008). The results presented here suggest that the neuroendocrine system structure is highly conserved in Lepidoptera, compared, for example, to Hemiptera or Coleoptera, where gene duplications and splicing variants, among other characteristics, seem to differ in a higher degree (Lavore et al, 2018; Veenstra, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, we observed that most of the particular paralogues and splicing variants initially detected in B. mori seem to be a characteristic of Lepidoptera rather than a possible consequence of domestication of the silkworm, as previously hypothesized (Roller et al, 2008). The results presented here suggest that the neuroendocrine system structure is highly conserved in Lepidoptera, compared, for example, to Hemiptera or Coleoptera, where gene duplications and splicing variants, among other characteristics, seem to differ in a higher degree (Lavore et al, 2018; Veenstra, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Thus, the presence of valine in position two is needed for optimal activity for ACPR whereas its absence in the same position (but on the AKH peptide) is necessary for optimal activation of AKHR-IA. Again, as discussed earlier, the importance of charged residues for optimal ACPR activity that are often found in insect ACPs (Hansen et al, 2010; Veenstra, 2019), whereas charged residues are unusually found on AKH peptides and are not well tolerated by AKH receptors that have been studied either in vivo or in vitro (Gäde, 1991; Gäde, 1993; Gäde et al, 1990). Finally, one clear finding from these studies is that ACP analogs that are too short (nonapeptide or octapeptide), even if they contain all the hallmark features, as demonstrated by the C-terminally truncated analogs for example, fail to activate ACPR.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, perhaps in common with AKH structural features, the switch between adjacent hydrophobic and hydrophilic residues is necessary in order to properly ‘fit’ and bind with its particular receptor (Gäde and Hayes, 1995) so that not only is the ACP analog shorter by one amino acid (a nonapeptide), but moreover, the entire structural configuration of the peptide is disrupted and the whole sequence is no longer in sync with its receptor. This corroborates with studies that have examined the conservation of the ACP primary structures across insects from different orders (including Diptera, Lepidoptera, Coleoptera, Hymenoptera and Hemiptera) as well as from various species within the same order (seventeen species of Coleoptera), where the N-terminal pentamer sequence, when the ACP system is present, is nearly completely conserved across these various species with a consensus motif of pQVTFS-, whereas significant sequence variability occurs within the C-terminus of the ACP sequence with deca-, nona- and even dodecapeptides reported (Hansen et al, 2010; Veenstra, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I analyzed transcriptome and genome SRAs using the tools from the SRAtoolkit (https:// www.ncbi.nlm.nih.gov/sra/docs/toolkitsoft/), Trinity (Grabherr et al, 2011) and Artemis (Rutherford et al, 2000) on the publicly available decapod genomes and draft genomes, as well as a large number of transcriptome (Table S1) and genome SRAs. Details of the methods that were used have been described in more detail elsewhere (Veenstra and Khammassi, 2017;Veenstra, 2019). A list of all SRAs used can be found in the supplementary data.…”
Section: Methodsmentioning
confidence: 99%